USE OF MOBILE APPLICATIONS IN TEACHING PROGRAMMING LANGUAGES TO STUDENTS OF THE HIGHER EDUCATION SYSTEM - Jalgasbaeva Shaxnoza Muratbay qizi (American Journals Publishing, 2024)
In this article, based on the possibilities of teaching programming languages to students of higher educational institutions of the Republic of Uzbekistan in depth, the convenience of teaching programming languages through the production of mobile applications, and online platforms for teaching programming are discussed is conducted.
Keywords: IT park, mobile application, programming languages, platform, Codecademy, Udemy, Coursera.